Efficacy of Topical Ethyl Chloride Spray versus Subcutaneous 1% Lidocaine Injection in Reducing Pain from One Rod System Implant Insertion - Monthinee Techasomboon; Rujira Wattanayingcharoenchai; Jittima Manonai Bartlett; Komkrit Aimjirakul (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives: To compare the efficacy of topical ethyl chloride spray and subcutaneous 1% lidocaine injection in reducing pain from one rod system implant insertion.Materials and Methods: Eighty-four women undergoing one rod implant insertion during February 2014 to December 2015 were enrolled and randomly allocated to ethyl chloride spray and 1% lidocaine injection groups. After skin was sterilized, the assigned anesthetic method was administered before insertion of one rod implant according to the standard pro-cedure. Pain during anesthetic administration, implant insertion, 20 min after insertion, and overall pain were evaluated, using a 100-mm visual analogue scale (VAS). Patient and doctor satisfaction were measured using a five-point Likert scale.Results: All basis clinical characteristics between two groups did not differ. There was no significant difference in VAS during and 20 min after implant insertion between 2 anesthetic groups (p > 0.05). Median VAS during anesthetic administration and overall pain in ethyl chloride spray group (1.50 and 1.60) were significant lower than lidocaine injection group (3.75 and 2.75) (p < 0.01). Patient and doctor satisfaction scores were significant higher in ethyl chloride spray group (p < 0.05).Conclusion: Ethyl chloride spray can be used as anesthetic option for one rod system implant insertion. It provides comparable analgesic effect to lidocaine injection but with less pain from anesthetic administration.